Peripapillary retinal leukemic infiltration associated with papilledema in a T-ALL patient without cranial or optic nerve involvement - ÇEKİÇ, OSMAN (WICHTIG PUBLISHING, 2016)
Purpose: To present a rare case of bilateral peripapillary retinal leukemic infiltration associated with papilledema without retrobulbar optic nerve involvement in a patient with acute lymphoblastic leukemia (ALL). Methods: This was a retrospective case report. Results: A 24-year-old man with T-cell ALL and 2-month history of papilledema presented to our department with reduction of visual acuity in the left eye. Visual acuity was 20/60 in the right eye and hand movements in the left eye. Fundus examination revealed grade 3 papilledema, bilateral peripapillary leukemic infiltration, and intraretinal hemorrhages. Cranial magnetic resonance imaging did not show any sign of cranial mass or optic nerve involvement. Pulse steroid therapy and oral acetazolamide was started. At day 18, visual acuity improved to 20/40 in the right eye and 20/60 in the left eye, while papilledema improved to grade 1 and hemorrhages regressed. Conclusions: To our knowledge, there is no other report of peripapillary leukemic infiltration in the absence of retrobulbar optic nerve involvement. We suspect that papilledema might have facilitated peripapillary retinal infiltration due to altered vascular permeability. The reverse could also be possible: leukemic infiltration leading to increase in vascular permeability may also contribute to papilledema.
Keywords: Leukemia; Leukemic infiltration; Papilledema; Retinal involvement